Non-Smad Signaling Pathways of the TGF-β Family - Zhang, Ying E (Cold Spring Harbor perspectives in biology, 2017)
Transforming growth factor β (TGF-β) and structurally related factors use several intracellular signaling pathways in addition to Smad signaling to regulate a wide array of cellular functions. These non-Smad signaling pathways are activated directly by ligand-occupied receptors to reinforce, attenuate, or otherwise modulate downstream cellular responses. This review summarizes the current knowledge of the mechanisms by which non-Smad signaling pathways are directly activated in response to ligand binding, how activation of these pathways impinges on Smads and non-Smad targets, and how final cellular responses are affected in response to these noncanonical signaling modes.